SIMON KRETZ, DANIEL KISS (eds.) - Relational Theories of Urban Form. An Anthology - Monclús Fraga, Javier (ZARCH, 2022)
Simon Kretz, Daniel Kiss (eds.) Relational Theories of Urban Form. An Anthology Basilea: Birkhäuser Verlag, 2021. 464 pp. Tapa blanda. Idioma: inglés. 29,95 € ISBN 978-3-0356-2076-4